2019
DOI: 10.15376/biores.14.2.4224-4235
|View full text |Cite
|
Sign up to set email alerts
|

Fuel properties of Indonesian bamboo carbonized at different temperatures

Abstract: Bamboo can be used in a variety of ways, including as fuel and as household and construction materials. Due to its versatility, the material is of high economic value. This study investigated the fuel properties of six bamboo species grown in Indonesia. Each bamboo sample was carbonized at different temperatures. Proximate and ultimate analyses were carried out on the bamboo samples. The thermal maturity of the bamboo samples as a solid fuel was investigated by the van Krevelen diagram. The efficiency of bambo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
15
1
Order By: Relevance
“…Recently, interest in bamboo utilization has increased alongside the demand for alternative wood and lignocellulosic raw materials. Several studies have reported the use of bamboo culm in various products, such as bioenergy (Park et al 2018(Park et al , 2019, composite materials (Febrianto et al 2012(Febrianto et al , 2015Maulana et al 2021a), and nanocellulose materials (Jang et al 2020;Rasheed et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest in bamboo utilization has increased alongside the demand for alternative wood and lignocellulosic raw materials. Several studies have reported the use of bamboo culm in various products, such as bioenergy (Park et al 2018(Park et al , 2019, composite materials (Febrianto et al 2012(Febrianto et al , 2015Maulana et al 2021a), and nanocellulose materials (Jang et al 2020;Rasheed et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…1) and ready availability. Bamboo occupies 3.2% of the world's forest area, with approximately 65% of all bamboo being grown in Asia (Park et al, 2019). Most bamboo species are distributed in the tropical and temperate zones; in Southeast Asia, there are 311 bamboo species, with 80-100 species distributed throughout Thailand (Sungkaew et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyl groups were destroyed due to thermal decomposition of the organic components, leading to a decrease in water absorption of biomass materials. Park et al (2019) found that the MC of andong, tali, kuning, ampel, and betung bamboo carbonized at 200 to 1,000 °C was lower than the untreated samples and increased with increasing carbonization temperature. Park et al (2020) highlighted that the MC of the control bamboo samples was 7 to 10% and decreased to less than 6% after carbonization, and the MC of carbonized bamboo increased as the carbonization temperature increased.…”
Section: Moisture Contentmentioning
confidence: 93%
“…As reported by Liu et al (2014), the VMC of bamboobiochar decreased as the carbonization temperature increased to 78.60% at 200 °C, 61.81% at 250 °C, and 41.34% at 300 °C. Park et al (2019Park et al ( , 2020 reported that the VMC of Indonesian bamboos carbonized at 200 °C to 1,000 °C showed a significant decrease at 200 °C to 400 °C and became constant after 600 °C. Kwon et al (2012) found that the VMC of Quercus variabilis wood carbonized at 400 °C to 1,200 °C decreased with increasing carbonization temperature.…”
Section: Volatile Matter Contentmentioning
confidence: 99%